The Rhetoric of Conspiracy Theories - Bennett, Sarah (2023)
Conspiracy theories are contentious narratives that claim to unveil a secret, malevolent plot by a group of conspirators. Research on conspiracy theories has been largely influenced by ‘the paranoid style’ (Hofstadter 2008); nevertheless, conspiracy theories are multifarious and complex narratives. They also hold persuasive powers – are rhetorical –and are widespread (Arnold 2008: 7, Goertzel 1994, Melley 2000). This thesis challenges the enduring association of conspiracy theories with paranoia by contributing to the growing body of work on socio-cultural approaches. In doing so, the current limitation of sparse intellectual engagement with the language of conspiracy theories is addressed by undertaking a socio- cognitive critical discourse analysis. This thesis also contributes to widening applications of socio-cognitive (critical) discourse studies (SCDS) by applying the approach to conspiracy theory discourse, both reinforcing and challenging its toolkit. Firstly, points of contact and divergence between diverse instantiations of conspiracy theories are demonstrated via the discursive construction of collective identities in the conspiracy milieu (Harambam and Aupers 2017: 125). Secondly, the persuasive properties of conspiracy theories and how proponents are positioned as enlightened victims are analysed. Thirdly, there is an exploration of how conspiracy theories can be replicated by a member of the general public. This thesis demonstrates how conspiracy theories can both critique and reinforce systemic power inequalities. SCDS provides analytical frameworks that elucidate the persuasive properties encoded in language. In addition, SCDS explicates the toolkit that conspiracy theories offer to essentially become a ‘DIY detective’ (Byford 2011), uncovering conspiracy theories either directly or vicariously. A variety of analytical frameworks are employed, including Koller’s framework for a socio-cognitive critical discourse studies (2019: 75), social actor framework (van Leeuwen 2008), Cap’s proximization model (2006, 2008, 2010, 2012, 2013a, 2013b, 2015), text world theory (Gavins 2007, Werth 1999) and the appraisal framework (Martin 2000, 2003; Martin and Rose 2003; Martin and Rose 2007; Martin and White 2007; White 1997 and 2002). As a data set for the study, representative texts have been chosen via a digital ethnographic process, including superconspiracy (Barkun 2003), ufology, conspirituality (Ward and Voas 2011) and celebrity death conspiracy theories.